Enhanced Photocatalytic Performance of Nanomaterial-Modified Dye-Sensitized Solar Cell (DSSC) Biosensors for Real-Time Biomedical Diagnostics - Chaudhary, Rakhee; Pawar, Vatsala; Garg, Urvija; Arora, Komal; Sharma, Nidhi; Prakash Saroj, Shashi; Dinesh, Dinesh; Sharma, Arun (Journal of Neonatal Surgery, 2025)
This research investigates the integration of nanomaterials into dye-sensitized solar cells (DSSCs) to enhance their photocatalytic performance and applicability in real-time biomedical diagnostics. The study focuses on the critical role of nanostructured materials, such as titanium dioxide (TiO2) and metal nanoparticles, in improving light absorption and charge transport within the solar cell structures. Through the incorporation of these nanomaterials, the efficiency of DSSCs is significantly elevated, leading to higher power conversion rates and improved sensor performance when utilized as biosensors for detecting biomolecules. The developed nanomaterial-modified DSSC biosensors exhibit rapid response times and high sensitivity, enabling effective monitoring of critical biomarkers in clinical settings. This innovative approach not only advances the capabilities of solar cell technology but also paves the way for the development of portable, low-cost diagnostic devices that can operate under ambient light conditions. The findings present valuable insights into the future of solar energy in conjunction with biomedical applications, offering promising solutions for point-of-care diagnostics.